Efficacy of Topiramate as Prophylactic Treatment of Severe Migraine in Children attending OPD of a Tertiary Care Hospital in Bangladesh- a Randomized Control Trial (Bangladesh Journal of Child Health, 2021)
Background: Migraine is the most common cause of severe recurrent headache in children. Flunarizine (FNZ) is safe and effective drug for prevention of migraine in children. Topiramate (TPM) is also successful as a preventive drug for migraine in children on randomized, double-blind, placebo-controlled trials.Objective: This study was done to observe the efficacy of Topiramate and also perform a comparison TPM and FNZ in patients with migraine of severe intensity in our situation.Materials & Methods: This was a randomized controlled trial done from January to July, 2018. This study was carried out in the OPD of Paediatric Neurology department, National Institute of Neurosciences, (NINS) Dhaka. Forty Children, 5-15 years old diagnosed as migraine with/without aura with severe intensity were randomized either as in study group (TPM treatment group) and control group (FNZ treatment group). Primary end point of the study was to find out the efficacy and safety of both TPM and FNZ after 4 months of treatment.Result: Post-treatment frequency of headache/month was significantly decreased in both groups (within group, p